Student and faculty perceptions on the rapid scale-up of medical students in Ethiopia. Issue 1 (December 2017) - Mengistu, Brittney; Vins, Holly; Kelly, Caitrin; McGee, Daphne; Spicer, Jennifer; Derbew, Miliard; Bekele, Abebe; Mariam, Damen; del Rio, Carlos; Blumberg, Henry; Comeau, Dawn
Abstract Background Ethiopia is a country of over 94 million people that has a severe physician shortage with approximately only 2.5 physicians per 100, 000 persons. Recently, the Ethiopian government implemented a "flood and retain" initiative to rapidly increase the quantity of physicians in Ethiopia. Consequently, medical student enrollment at Addis Ababa University (AAU) School of Medicine increased from 100 to approximately 300–400 students per class. This study evaluated the impact of the rapid scale-up in the number of medical students on the quality of medical education at AAU and the impact of the U.S. government-funded Medical Education Partnership Initiative (MEPI) grant awarded to AAU to provide resources to strengthen the quality of medical education at AAU. Methods Qualitative, semi-structured, in-depth interviews were conducted with 22 key informants including faculty members, administrators and medical students at AAU. The audio recordings were transcribed verbatim and interview data were analyzed with thematic analysis. Results Four key themes emerged from the data. Overall, participants perceived a decrease in the quality of medical education at AAU due to challenges created by the rapid scale-up in the number of medical students. Positive learning environments were described as difficult to achieve due to overcrowding in classrooms and the limited numbers of textbooks. Overall, participants stated that infrastructure improvement is needed to provide adequate medical student training. The medical education initiatives implemented and funded by MEPI have provided significant resources to support the medical student curriculum but additional resources are required to accommodate a large student body. Conclusions The unprecedented rapid scale-up of medical students has impacted multiple facets of medical education at AAU. It is important to consider the perspectives of students and faculty in order to focus future medical education policies, MEPI programming and the allocation of resources.